Direct Disk Diffusion Testing and Antimicrobial Stewardship for Gram-Negative Bacteremia in the Context of High Multidrug Resistance - Wantin Sribenjalux; Pawarit Kulwongroj; Waewta Kuwatjanakul; Lumyai Wonglakorn; Kanuengnit Srisak; Natapong Manomaiwong; Atibordee Meesing (Antibiotics)
Background: Combining direct disk diffusion (DD) testing with antimicrobial stewardship (AMS) may optimize antibiotic use and improve outcomes in patients with Gram-negative bloodstream infections (GNBSIs). Methods: This quasi-experimental study was conducted at Srinagarind Hospital, Khon Kaen University, between 13 September 2022 and 11 April 2023. Patients with GNBSIs were enrolled during two phases: a standard care phase (13 September 2022–2 January 2023) and an intervention phase (16 January 2023–11 April 2023), during which therapy adjustments were guided by DD results interpreted by infectious disease specialists. Results: Among the 141 patients included (68 in the standard care group and 73 in the intervention group), the mean age was 61.7 years, and 60.2% were male. Escherichia coli (36.5%) and Klebsiella pneumoniae (27.6%) were the most frequently isolated pathogens, with intra-abdominal and urinary tract infections being the most common sources. Multidrug-resistant (MDR) organisms were identified in 48.9% of cases. Compared to standard care, the intervention group had a significantly shorter median time to optimal therapy (40.0 vs. 59.1 h, p = 0.037) and a higher proportion of patients receiving optimal therapy within 72 h (86.2% vs. 62.3%, p = 0.002). While 30-day mortality did not differ significantly between groups (17.2% vs. 16.7%, p = 0.98), MDR bacteremia and ICU admission were associated with increased mortality. In contrast, receiving optimal therapy within 72 h was associated with reduced mortality. Conclusion: Direct DD testing combined with AMS significantly reduced the time to optimal antibiotic therapy and decreased inappropriate antibiotic use in GNBSI patients. Achieving optimal therapy within 72 h was associated with a trend toward reduced mortality.